Imagining and Enacting Métis-Informed Anti-Racist Education: A Local Prairie K–12 Flower Beadwork Framework - Gillies, Carmen; Mercereau, Nicole; Pocha, Sheila (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
This article is based on findings from an anti-racist Métis/Michif partnership between the Gabriel Dumont Institute’s Saskatchewan Urban Native Teacher Education Program (SUNTEP) and the University of Saskatchewan’s College of Education. The study took a local approach through a series of anti-racist knowledge exchanges amongst 16 urban and surrounding-area Prairie Métis teachers and teacher educators. Drawing from Métis teachers’ experiences, Métis studies, and critical race theory, the article disrupts Eurocentric conceptions of anti-racist education by centring Métis experiential knowledge. Through qualitative and Métis methods, data was collected from five workshops that revealed an initial Métis-informed anti-racist education (MIARE) K–12 flower beadwork framework. The framework demonstrates how specific experiences of K–12 racialization are transformed into anti-racism through Métis teachers’ intergenerational cultural knowledge protected by core Métis cultural values.